Автоматизація безконтактного контролю температури тіла співробітників для дозволу доступу на підприємство - Домущей, Д. С. (ХНУРЕ, 2021)
The article discusses an automated contactless body temperature control system, which is a software and hardware complex. The main task of this system is to measure and maintain statistics on changes in the body temperature of employees in electronic form. This can be used to prevent the spread of a viral infection. Thus, working time will be saved, which will not be spent on manual temperature measurement by a nurse and the likelihood of illness of employees in the enterprise will be reduced.
Keywords: безконтактний контроль температури тіла; дозвол доступу на підприємство